A new type of high hardness coating for improving drill bit stability in unconventional oil and gas development - Xuan, Lingchao; Wang, Jiangshuai (Frontiers in Energy Research, 2023)
In deep unconventional oil and gas development, the problem faced is that PDC bits are eroded by solid-liquid high-speed fluids, resulting in damage. It has led to serious damage to the stability of the drill bit, a decrease in the service life of the drill bit, and an increase in the difficulty in efficient drilling. The essence is that the surface hardness and erosion resistance of the drill bit are not strong enough. Therefore, improving the stability of drill bits is a crucial and urgent problem to be solved. In this paper, Ni60A + 20% WC + 0.3% graphene composite coatings were prepared on a Q235 steel substrate, which is a new type of high hardness coating. Moreover, the effects of microstructure and microhardness of the composite coatings at different laser powers (800 W, 1200 W, 1600 W, and 2000 W) were investigated. The results show that the laser power can significantly affect the microstructure of the coating. The phase composition of the composite coatings is essentially the same at different laser powers. However, there are significant differences in the content of each phase. When the laser power is higher than 1200W, the content of M23C6, Cr3C2 and Fe3C in the composite coating increases and the microhardness of the coating decreases. When the laser power is below 1200 W, the dilution rate of the substrate is low and a metallurgical bond cannot be formed between the composite coating and the substrate.